2013
DOI: 10.1093/intimm/dxs155
|View full text |Cite
|
Sign up to set email alerts
|

Transport of misfolded endoplasmic reticulum proteins to the cell surface by MHC class II molecules

Abstract: Nascent MHC class II molecules are associated with the invariant chain and are transported to the endolysosomal pathway, where MHC class II molecules acquire peptide antigens. On the other hand, misfolded endoplasmic reticulum (ER) proteins are generally degraded in the cells and are neither expressed on the cell surface nor secreted. Here, we found that MHC class II molecules associate with some misfolded ER proteins via the peptide-binding groove in competition with invariant chain. The misfolded proteins as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 30 publications
(36 reference statements)
1
45
0
Order By: Relevance
“…32 Furthermore, intact IgG heavy chain is transported to the cell surface by HLA class II molecules via association with the peptide-binding groove, and IgG heavy chain/ HLA class II complexes are recognized by autoantibodies in rheumatoid factor-positive sera from RA patients. 33 In contrast, autoantibodies in rheumatoid factor-positive sera from non-RA individuals did not bind to IgG heavy chain/HLA class II complexes, suggesting that IgG heavy chain complexed with HLA-DR is a specific target for autoantibodies from RA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Furthermore, intact IgG heavy chain is transported to the cell surface by HLA class II molecules via association with the peptide-binding groove, and IgG heavy chain/ HLA class II complexes are recognized by autoantibodies in rheumatoid factor-positive sera from RA patients. 33 In contrast, autoantibodies in rheumatoid factor-positive sera from non-RA individuals did not bind to IgG heavy chain/HLA class II complexes, suggesting that IgG heavy chain complexed with HLA-DR is a specific target for autoantibodies from RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, we found that misfolded proteins are rescued from degradation and transported to the cell surface without processing to peptides when they associate with the peptide-binding groove of HLA class II molecules in the endoplasmic reticulum (ER). 32,33 Structural analyses of major histocompatibility complex (MHC) class II molecules have revealed that both ends of the MHC class II peptide-binding groove are open. Therefore, it is possible that MHC class II molecules might bind linear epitopes exposed on misfolded proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Unexpectedly, we discovered that these misfolded HLA class I molecules were transported to the cell surface by association with the peptide-binding groove of HLA class II molecules (8). Indeed, direct association between HLA class II molecules and misfolded HLA class I molecules was detected in HLA class II-expressing B-cell lines.…”
Section: −5mentioning
confidence: 94%
“…HLA-Cw3-pep-HLA-DRB1*04:04 containing a covalently attached peptide was generated by adding the peptide sequence (Cw3: GSHSMRYFYTAVSRPGR) and linker (GSGSGS) between the signal sequence and extracellular domain of these MHC class II cDNA as previously described (35). A cDNA for the mutHEL in which two cysteine residues at positions 30 and 64 were replaced with alanine was generated as described (8). V regions of RF61 RF mAb were synthesized according to the published sequence (accession numbers: for heavy chain, X54437; λ chain, X54438).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation